PENGARUH FEE BASED INCOME DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP TINGKAT PROFITABILITAS (Media Riset Akuntansi, 2022)
This study aims to determine the effect of fee-based income and operating expenses operating income on profitability. The sample of this study consisted of 20 state-owned commercial bank banking sector companies listed on the Indonesia Stock Exchange in 2013-2017. The method used in this research is multiple linear regression analysis. The results showed that fee-based income had no significant effect on profitability (ROA), operating expenses operating income had a significant negative effect on profitability, ROA and fee-based income and operating expenses operating income simultaneously had a significant effect on profitability variables (ROA).